Isosorbide synthesis from cellulose with an efficient and recyclable ruthenium catalyst. Issue 19 (22nd August 2017) - Keskiväli, Juha; Rautiainen, Sari; Heikkilä, Mikko; Myllymäki, Teemu T. T.; Karjalainen, Jaakko-Pekka; Lagerblom, Kalle; Kemell, Marianna; Vehkamäki, Marko; Meinander, Kristoffer; Repo, Timo
Abstract : A recyclable Ru-based hydrogenation catalyst for the two-step conversion of lignocellulosic substrates into isosorbide. Abstract : Herein, we describe an efficient two-step pathway for isosorbide synthesis from cellulose with the use of new recyclable Ru-catalysts. We show that the oxidative and sulfonation treatments of the new Ru-catalysts increase the acidity and the hydrophilicity of the activated carbon support material, thus reducing the catalyst fouling caused by the build-up of insoluble products. Accordingly, the new Ru-catalysts are more resilient towards lignin containing cellulose than a commercial Ru/C catalyst, and the best Ru-catalyst maintains its high catalytic activity in four consecutive runs with dissolving pulp, microcrystalline cellulose and even with residual lignin containing bagasse pulp. Overall, our two-step approach provides isosorbide in high yields of 56–57 mol% (49–50 wt% of the substrate) from the cellulosic substrates.